Persepsi Mahasiswa Ilmu Politik Terhadap Baliho Calon Legislatif - Yati Fadilah; Petrick Stiven; Lili Hasanah; Muhammad Gilang Pratama (CV. ITTC INDONESIA, 2023)
This research aims to explore political science students' perceptions of the use of billboards for legislative candidates in the context of general elections in Indonesia. Involving 24 respondents, this research used quantitative methods with simple linear regression analysis to identify factors that influence students' perceptions of billboards for legislative candidates. The results of the questionnaire show that the majority of respondents agree or strongly agree with the influence of billboards in general elections, with the level of satisfaction with political decisions as the most dominant aspect. Although there are variations in opinion, the main conclusion is that billboards for legislative candidates have a significant influence in influencing the perceptions and decisions of political science voters. This research contributes to the understanding of democratic practices and participatory politics among political science students and provides a basis for improvement or innovation in the use of billboards for legislative candidates to make them more effective.